Experimental study on the influencing factors of permeability of sand media - Zongjun GAO; Ziqi DING; Jiutan LIU; Wenyue LIU (Shuiwen dizhi gongcheng dizhi)
The Darcy test is the primary method for determining the permeability of sand media. However, factors such as particle size and compaction of the sand medium, differences between the total dissolved solids (TDS) and the head of the water, and the test temperature, leading to great differences in the results of the Darcy test, cause great uncertainty to the practical application. To explore the variability in Darcy’s test results under different conditions, different sand media were selected under normal temperature and pressure, and tests were carried out considering varying temperatures, TDS, and poor water supply and drainage heads. The results show that the higher the water temperature, the higher the hydraulic conductivity, the better the permeability, and the more significant the influence of temperature. Higher TDS decreases the permeability. In media with high permeability, changes in hydraulic conductivity due to variations in TDS follow a power or exponential function, with low TDS causing drastic changes, while for poorly permeable media, hydraulic conductivity decreases linearly as TDS increases. When the difference between water supply and drainage head reaches a certain value, the hydraulic conductivity is no longer constant, with the limit Reynolds number of 0.4 for fine sand and 3.3 for medium sand. The higher the degree of compaction, the smaller the hydraulic conductivity. when the porosity is the same, the larger the particle size, the greater the hydraulic conductivity. The test findings provide valuable information for the acquisition and application of hydraulic conductivity in the future, and also provide a basis for the selection of hydrogeological parameters such as groundwater evaluation and geological disaster prevention.